Angiogenic, inflammatory and immunologic markers in predicting response to sunitinib in metastatic renal cell carcinoma. Issue 9 (20th August 2017) - Mizuno, Ryuichi; Kimura, Go; Fukasawa, Satoshi; Ueda, Takeshi; Kondo, Tsunenori; Hara, Hidehiko; Shoji, Sunao; Kanao, Kent; Nakazawa, Hayakazu; Tanabe, Kazunari; Horie, Shigeo; Oya, Mototsugu; et al.
Abstract : The objective of this prospective study was to identify baseline angiogenic and inflammatory markers in serum as well as the baseline levels of immune cells in whole blood to predict progression‐free survival in patients with metastatic renal cell carcinoma treated with sunitinib. Blood samples were collected at baseline in all 90 patients to analyze serum angiogenic and inflammatory markers together with peripheral blood immunological marker. The association between each marker and sunitinib efficacy was analyzed. Univariate and multivariate Cox proportional model analyses were used to assess the correlation between those markers with survival. Baseline levels of interleukin‐6, interleukin‐8, high sensitivity C‐reactive protein and myeloid‐derived suppressor cells were significantly higher in patients who progressed when compared with those with clinical benefit. Analysis by the Cox regression model showed that baseline interleukin‐8, high sensitivity C‐reactive protein and percentage of T helper type 1 cells were significantly associated with progression‐free survival in univariate analysis. Furthermore, in multivariate analysis, those three markers were independent indices to predict progression‐free survival. In conclusion, angiogenic (interleukin‐8), inflammatory (interleukin‐6, high sensitivity C‐reactive) and immunologic (myeloid‐derived suppressor cells, percentage of T helper type 1 cells) markers at baseline would predict the response to sunitinib therapy and/or disease progression in patients with metastatic renal cell carcinoma. Abstract : Angiogenic (interleukin‐8), inflammatory (interleukin‐6, high sensitivity C‐reactive), and immunologic (myeloid‐derived suppressor cells, percentage of T helper type 1 cells) markers at baseline would predict response to sunitinib therapy and/or disease progression in patients with mRCC.